ELAV and FNE Determine Neuronal Transcript Signatures through EXon-Activated Rescue. - Carrasco, J.; Rauer, M.; Hummel, B.; Grzejda, D.; Alfonso-Gonzalez, C.; Lee, Y.; Wang, Q.; Puchalska, M.; Mittler, G.; Hilgers, V. (Molecular Cell, 2020)
The production of alternative RNA variants contributes to the tissue-specific regulation of gene expression. In the animal nervous system, a systematic shift toward distal sites of transcription termination produces transcript signatures that are crucial for neuron development and function. Here, we report that, in Drosophila, the highly conserved protein ELAV globally regulates all sites of neuronal 3' end processing and directly binds to proximal polyadenylation sites of target mRNAs in vivo. We uncover an endogenous strategy of functional gene rescue that safeguards neuronal RNA signatures in an ELAV loss-of-function context. When not directly repressed by ELAV, the transcript encoding the ELAV paralog FNE acquires a mini-exon, generating a new protein able to translocate to the nucleus and rescue ELAV-mediated alternative polyadenylation and alternative splicing. We propose that exon-activated functional rescue is a more widespread mechanism that ensures robustness of processes regulated by a hierarchy, rather than redundancy, of effectors.